PEMIKIRAN-PEMIKIRAN ALTERNATIF TERHADAP PEMBANGUNAN - Yuni Prihadi Utomo (Muhammadiyah University Press, 2001)
Development is one of urgent concept in this age. The problem of development is wide and complicated, therefore development often become underdevelopment in reality. In this case, the writer provides four idea of development; there are International Dependence Approach, Neo Structural Thought, New Structural Transformation Model from Berkeley, and Political Approach of Development. From those thoughts, the writer gives final notes that development is too complex if it is discussed only from economic sector. Development is a continuous process improvement of a society on such ideology, political, social and cultural system that entirely direct to better life and more humane.